The logic of migratory crisification: a conceptual proposal for analyzing contemporary discourses and practices - Estrada Villaseñor, Cecilia (My University, 2026)
.

Introduction: This article proposes the concept of migratory crisification as an analytical framework to understand how certain dynamics of human mobility are systematically framed as social, political, and media crises. While the notion of a “migration crisis” has become pervasive in public discourse, it is rarely interrogated as a socially constructed category. We argue that crisification operates as a discursive, institutional, and affective process through which migration is transformed into an exceptional threat, legitimizing extraordinary political and policy responses. The frequent conflation between migration and refuge or asylum further intensifies this dynamic, particularly in contexts where violence or insecurity does not stem from internationally recognized armed conflicts.Methods: The study employs a qualitative research design combining critical discourse analysis and comparative media analysis. The empirical corpus consists of 72 news articles published in the Spanish press across four key moments in the public framing of migration (2006, 2014, 2022, and 2024). These cases were selected due to their prominence in national debates and their association with distinct migratory routes and policy responses. The analysis is informed by theoretical contributions from securitization theory, moral panic scholarship, and studies on the governance of migration.Results: The findings identify three interrelated mechanisms that structure migratory crisification: (1) alarmist narratives that frame migration as an imminent threat; (2) the institutionalization of exceptionality through emergency policies and restrictive border practices; and (3) the mobilization of collective emotions, such as fear or selective solidarity, which shape public perception and political legitimacy.Discussion: By conceptualizing crisification as a socio-political process rather than an objective condition, this article contributes to denaturalizing the automatic association between migration and crisis and offers a framework for critically examining how such narratives are produced, circulated, and institutionalized in contemporary migration governance.
Artículos en revistas